PENDEKATAN DALAM PROSES BELAJAR: KAJIAN KITAB AYYUH? AL-WALAD: KAJIAN KITAB AYYUH? AL-WALAD - Mudhoffar (LP3M IAI Al-Qolam Malang, 2018)
Learning is a very essential human need. Learning can develop human potency, both physical and spiritual. Learning is also an obligation that must be done by every human being. Approach in the learning process is needed so that students can get useful knowledge. From this background the writer will discuss it in an article entitled